2019
DOI: 10.3389/fpls.2019.00726
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Protein-Protein Interactions in the Ethylene Pathway in the Different Ethylene Receptor Subfamilies

Abstract: Signal perception and transmission of the plant hormone ethylene are mediated by a family of receptor histidine kinases located at the Golgi-ER network. Similar to bacterial and other plant receptor kinases, these receptors work as dimers or higher molecular weight oligomers at the membrane. Sequence analysis and functional studies of different isoforms suggest that the ethylene receptor family is classified into two subfamilies. In Arabidopsis , the type-I subfamily has two members (ETR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 79 publications
2
15
0
Order By: Relevance
“…The homomeric affinities of the AHK1 osmosensor strongly resemble the affinities observed for other sensor histidine kinases like AtETR1 and AtETR2 [7]. The same experimental setup and method, under which a dissociation constant of 208 nM was observed in this study for AHK1, showed values of 326 nM and 96 nM for AtETR1 and AtETR2 respectively [7]. The in vitro MST results of AHK1 homomerization were confirmed by two independent in vivo approaches, namely yeast mbSUS and in planta FRET-FLIM.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The homomeric affinities of the AHK1 osmosensor strongly resemble the affinities observed for other sensor histidine kinases like AtETR1 and AtETR2 [7]. The same experimental setup and method, under which a dissociation constant of 208 nM was observed in this study for AHK1, showed values of 326 nM and 96 nM for AtETR1 and AtETR2 respectively [7]. The in vitro MST results of AHK1 homomerization were confirmed by two independent in vivo approaches, namely yeast mbSUS and in planta FRET-FLIM.…”
Section: Discussionsupporting
confidence: 77%
“…Remarkably, despite the apparent monomeric state under size exclusion chromatography conditions, the functionality of AHK1 in terms of potential to form homodimers could be shown in MST. The homomeric affinities of the AHK1 osmosensor strongly resemble the affinities observed for other sensor histidine kinases like AtETR1 and AtETR2 [7]. The same experimental setup and method, under which a dissociation constant of 208 nM was observed in this study for AHK1, showed values of 326 nM and 96 nM for AtETR1 and AtETR2 respectively [7].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It is unclear if dimerization between kinase domains of the other receptor isoforms occurs. It has also been suggested that heterodimers are possible (35,50). Evidence that these are receptors is that all of these proteins bind ethylene with high affinity (41,47,51,52) and specific mutations in any one of these proteins leads to ethyleneinsensitivity (36,(38)(39)(40)53).…”
Section: Ethylene Signaling Components and The Canonical Pathwaymentioning
confidence: 99%
“…The initiation of ethylene signal transduction begins with the perception of ethylene by the ethylene receptor family: ETHYLENE RESPONSE 1 (ETR1), ETHYLENE RESPONSE SENSOR 1 (ERS1) which are type-I subfamily, ETHYLENE RESPONSE 2 (ETR2), ETHYLENE-INSEN-SITIVE 4 (EIN4), and ETHYLENE RESPONSE SENSOR 2 (ERS2), a type-II subfamily, at the endoplasmic reticulum (ER) where the receptor can form a homomer or heteromer between different subfamilies (Berleth et al 2019). The signalling pathway continues from a transmembrane protein, ETHYLENE-INSENSITIVE 2 (EIN2), to transcription factor, ETHYLENE-INSENSITIVE 3 (EIN3)/ EIN3-LIKE1 (EIL1), to target genes encoding transcription factors such as ERF, WRKY and NAC family genes, or directly regulates gene expression (Dolgikh et al 2019).…”
Section: Ethylene Signallingmentioning
confidence: 99%